Digital Transformation and Fraud Challenges: Cybersecurity Analysis in Indonesian State-Owned Enterprises Using The Heptagon Framework - Maharani, Azalia Nadya Ayu; Pamungkas, Imang Dapit (International Journal of Accounting and Economics Studies, 2025)
Fraud and cyber-related threats represent critical challenges to the integrity of state-owned enterprises (SOEs), particularly during their on-‎going digital transformation efforts aimed at improving transparency and operational efficiency. This study investigates how the Fraud Hep-‎tagon framework, digital forensic techniques, and risk management practices collectively contribute to mitigating fraudulent activities and ‎enhancing the reliability of SOE information systems. A mixed-methods design was applied, integrating qualitative and quantitative ap-‎proaches. The qualitative strand involved semi-structured interviews with 25 participants, including IT managers, cybersecurity personnel, ‎and internal auditors, to identify the underlying drivers of fraud in SOEs. Meanwhile, the quantitative strand examined the effectiveness of ‎digital forensic practices in minimizing the likelihood of financial statement manipulation, drawing on secondary datasets. The qualitative ‎findings highlight that systemic pressures, operational inefficiencies, and institutional vulnerabilities are dominant factors influencing ‎fraudulent conduct. Conversely, technology-enabled controls and risk-based mechanisms significantly strengthen monitoring, detection, and ‎accountability. The quantitative results further validate that digital forensic applications play a substantial role in fraud prevention. Collective-‎ly, the evidence suggests that fraud within SOEs is predominantly systemic rather than individual in nature, underscoring the necessity for ‎integrated interventions across behavioral, technological, and governance dimensions. By combining the Fraud Heptagon perspective with ‎digital forensic methodologies and structured risk management frameworks, organizations can establish more robust strategies to prevent ‎and mitigate fraudulent practices, while simultaneously reinforcing the dependability of information systems. The insights derived from this ‎research provide actionable recommendations for policymakers, corporate governance authorities, and financial professionals, while also ‎laying the groundwork for comparative studies across sectors and organizational settings. Ultimately, this study advances the global dis-‎course on fraud prevention and cybersecurity in the context of digitally evolving enterprises‎.